Analisa Peran DPS Dalam Pengawasan Perbankan Syariah Di Indonesia - Merisa Duwi Lestari; Agustina Eka Melinda; Melinda Indra Sari; Agus Eko Sujianto (Pusat Riset dan Inovasi Nasional, 2023)
This research presents the Dewan Pengawas Syariah (DPS) in Islamic Financial Institutions, which plays a part in supervision and is responsible for Islamic teachings. Based on the research findings, it is expected that the members of the board have a deep understanding in the fields of fiqh muamalah, finance, and economics. The functions and characteristics of DPS in Islamic banking are intertwined with influential networks that align with the management of Islamic banking risks, such as reputational risk, which ultimately affects other risks, such as liquidity risk. DPS has the responsibility to ensure that various products and actions of Islamic banks are in line with the principles of Sharia. This research includes relevant literature reviews. The objective of this research is to elucidate the role of DPS in Islamic banking. The analysis adopts a descriptive-analytical approach, which means the researcher needs to dissect and describe the investigated issues. Data collection is conducted through document reviews and literature sources.